Resource potential and extraction technique design for helium in coal measures - Lei WANG; Maoyin TANG (Meitian dizhi yu kantan)
Back groundHelium is an important strategic scarce resource. Presently, helium used in industry originates primarily from natural gas. In contrast, helium in coal measures, generally emerging as coalbed methane (CBM) with a high helium content, serves as a vital supplement to conventional helium resources. In industry, helium extraction from boil off gas (BOG) during natural gas liquefaction is recognized as an important way to obtain helium resources. However, existing studies on helium in coal measures mostly focus on the genesis, enrichment patterns, and geochemical characteristics of helium, while there is a lack of studies on its resource characteristics and extraction techniques.MethodsThis study investigated the helium resources in coal measures in the Sanjiaobei Block along the northeastern margin of the Ordos Basin as an example to analyze the characteristics of regional helium resources. Furthermore, a technique for helium extraction from natural gas in the block was designed based on a existing liquefied natural gas (LNG) plant in the block. ResultsThe results indicate that the Sanjiaobei Block features abundant coal-measure gas but relatively low helium resources. Crust-derived helium is identified in this block, with molar volumetric fractions ranging from 0.01% to 0.30% (average: 0.07%). This establishes the Sanjiaobei Block as the low-helium area. Nevertheless, the helium resources in this block prove stable generally, with geological reserves and cumulative production reaching up to 11.1456 million m3 and 0.7007 million m3, respectively. Therefore, these helium resources can be treated as a feed gas source for helium extraction. This study conducted helium extraction from BOG produced during LNG production. The low-temperature helium extraction technique was selected, for which the two-tower separation technique combining pre-expansion refrigeration and nitrogen cycle refrigeration was employed. The helium extraction process consisted of six units: gas filtration, catalytic dehydrogenation, dehydration and drying, helium extraction, helium charging, and liquid oxygen catalysis. ConclusionsThe design proposed in this study adopts a nitrogen circulation system (NCS) for efficient refrigeration and optimizes energy recovery, reducing the dependence on direct compression of feed gas. Furthermore, this design provides a stable low-temperature environment that is insensitive to helium concentration fluctuations, enabling the rational and full utilization of BOG gas produced in the plant. This renders the design especially suitable for efficient extraction of low-abundance helium resources produced in the plant. The findings of this study will play a positive and significant role in improving both the technique for helium extraction in coal measures and the economic benefits of relevant enterprises.